Synthesis and Antimicrobial and Antioxidant Activities of Some New 5-(2-Methyl-1H-indol-3-yl)-1,3,4-oxadiazol-2-amine Derivatives - Anand R. Saundane; Vaijinath A. Verma; Vijaykumar T. Katkar (Journal of Chemistry)
A series of 5-(2-methyl-1H-indol-3-yl)-1,3,4-oxadiazol-2-amine derivatives (3–5) were synthesized. These previously unknown compounds were characterized by spectral studies and elemental analysis. These compounds were evaluated for their antimicrobial and antioxidant activities. Among all the compounds tested 5d exhibited promising antibacterial, antifungal, radical scavenging, and ferric ions (Fe3+) reducing antioxidant power (FRAP) activities, whereas the compounds 3b, 4c, and 5e exhibited good FRAP and metal chelating activities. In general compounds containing chloro and methyl substituent exhibited better antimicrobial and antioxidant activities.